Aboveground biomass and carbon storage Of Rhizophora Spp. In delta Tumpat - Sheikh Kamal, Syarifah Haniera (2018)
Removal of mangrove forest will affect the ecosystems thus the development of the carbon cycle will be disturbed. A study was conducted in five islands in Delta Tumpat, Kelantan to study the aboveground biomass and carbon storage of Rhizophora spp. in mangrove forest. A total of 491 trees belong to Rhizophora apiculata and Rhizophora mucronata were measured. The average diameter for all islands is 6.27 cm. Aboveground biomass in this study were calculated using equation by Komiyama el al., (2005). Total AGB for five areas is 67.03 tan/ha with 2.90 tan/ha (Pulau Tujuh), 4.11 tan/ha (Pulau Bedal A), 1.53 tan/ha (Pulau Bedal B), 24.44 tan/ha (Pulau Mas) and 34.05 tan/ha (Pulau Layang-layang). Carbon stock are calculated 49% from AGB with given value of 1.42 tanC/ha (Pulau Tujuh), 2.01 tanC/ha (Pulau Bedal A), 0.75 tanC/ha (Pulau Bedal B), 11.98 tanC/ha (Pulau Mas), 16.69 tanC/ha (Pulau Layang-layang) and the total is 32.85 tanC/ha respectively. A further study should be implemented here to gather more data in helping related organisation with mangrove management and conservation plan.